Effect Of Zinc Administration in Preventing Ethambutol-Induced Optic Neuropathy in Wistar Rats Model - Riski Prihatningtias; Disti Hardiyanti; Maharani Maharani; Arief Wildan; Arnila Novitasari Saubig; Hermawan Istiadi (Journal of Biomedicine and Translational Research, 2023)
Background: Ethambutol-induced optic neuropathy (E-TON) is one of the most common optic neuropathies, especially in developing countries with an increasing rate of Tuberculosis (TB). Various outcomes of visual impairment that may lead to permanent visual loss makes it imperative to prescribe supplementation to prevent E-TON. Zinc supplementation is suggested as one of many to prevent E-TON given that ethambutol is a Zn chelator.Purpose: To analyze the apoptosis rate of retinal ganglion cell (RGC) in Wistar rats given ethambutol and Zinc supplementation.Methods: Experimental analysis research. True – experimental design and post-test only using Wistar rats. Subjects were divided into 2 groups, treatment grup was given Ethambutol and Zn and control group was given ethambutol without Zn for 30 days. Assessment of apoptosis rate was concluded by an anatomical pathologist with histopathological scoring using Hematoxylin Eosin staining. Differences between two grups were statistically analyzed using Mann Whitney U test, (Signifikan p <0,05).Results: From Distribution of rate apoptosis in treatment group was found 28.6% without apoptosis, 71.4% score 1 and no score > 1. There was a significantly different in apoptosis retinal ganglion cell between two grups (p= 0.015).Conclusion: The rate of retinal ganglion cell apoptosis was lower in rats treated ethambutol with Zn than without Zn.